Valuation for cuttins rebar ot foundation pile - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the valuation for Cuttins Rebar of foundation piles of BRACU new campus project site